Privatisation and culture - Čopič, Vesna (Družboslovne razprave, 1999)
The new circumstances determined by political pluralism, a market economy and social stratification also require the transformation of cultural policy. Instead of the present-day transition, which only adapts old positions to a new environment, a strategic transformation that would improve quality and content is needed. The author believes that such a qualitative transformation calls for the redefinition of the role of the state in culture. The state used to have all three basic functions: the regulation of cultural activities; the provision of cultural services through state cultural institutions; and the subsidising of individual cultural projects. In order to establish the principles of competition, selection, transparency and accountability in the allocation of public funds for culture, the funding of cultural activities must be separated from their provision. This article will try to advance a number of arguments as to why civil society is the most appropriate partner for assuming the function of the organisation and performance of cultural services from the state, and why the state should now concentrate more on the newly-formed strategic role for culture-policy formation, i.e. establishing the general conditions for cultural development whereby a range of stakeholders, including the private and civil sectors, is brought to the surface.
Keywords: culture; kultura; kulturna politika; autonomy; avtonomija; privatizacija; organizacija; organization